Enhanced performance of porous silicone-based dielectric elastomeric composites by low filler content of Ag@SiO2 Core-Shell nanoparticles - Lian Xiong (Taylor & Francis Group, 2018)
In the present work, micropores and a low filler content of Ag@SiO2 nanoparticles (NPs) are synchronously introduced into polydimethylsiloxane (PDMS) film to obtain porous dielectric elastomeric composites. The morphology and dielectric and mechanical properties of the composites are investigated. The resulting composites possess high dielectric permittivity, low dielectric loss and low Young’s modulus, which is beneficial to the requirements of a dielectric elastomer actuator. This study provides an effective method to prepare high-performance PDMS-based dielectric porous dielectric elastomeric composites filled with low filler contents of Ag@SiO2 NPs.